USP9X deletion elevates the density of oligodendrocytes within the postnatal dentate gyrus. Issue 1 (1st January 2016) - Oishi, Sabrina; Zalucki, Oressia; Premarathne, Susitha; Wood, Stephen A.; Piper, Michael
ABSTRACT: Neural stem cells (NSCs) within the adult hippocampal dentate gyrus reside in the subgranular zone (SGZ). A dynamic network of signaling mechanisms controls the balance between the maintenance of NSC identity, and their subsequent differentiation into dentate granule neurons. Recently, the ubiquitin-specific protease 9 X-linked (USP9X) was shown to be important for hippocampal morphogenesis, as mice lacking this gene exhibited a higher proportion of proliferating NSCs, yet a decrease in neuronal numbers, within the postnatal dentate gyrus. Here we reveal that Usp9x -deficiency results in the upregulation of numerous oligodendrocytic and myelin-associated genes within the postnatal hippocampus. Moreover, cell counts reveal a significant increase in oligodendrocyte precursor cells and mature oligodendrocytes per unit volume of the mutant dentate gyrus. Collectively, these findings indicate that USP9X may regulate NSC lineage determination within the postnatal SGZ.